The Impact of Sodium Fluoride on Redox the Impact of Sodium Fluoride on Redox Homeostasis an Antioxidant Defense Systems in Sperm Cells: an in Vitro Study - Bardas Ozkan, Ebru; Tanyildizi, Sadettin; Ulas, Mustafa; Uslu, Hamit; Uslu, Gozde Atila; Odabasi, Mehtap (Int Soc Fluoride Research, 2025)
Purpose: Fluoride is a ubiquitous element in nature that can be beneficial at low doses but toxic at high levels. The Holstein bulls used in this study are both economically significant and represent a species susceptible to environmental fluoride exposure through contaminated water and feed. The research seeks to evaluate the impact of sodium fluoride (NaF) on sperm function in farm animals, mimicking field conditions, and thereby elucidate potential effects on fertility. This is also of significant importance for food safety. This study aimed to investigate the effects of NaF on redox homeostasis and antioxidant defense mechanisms in bovine sperm cells. Methods: Sodium fluoride was applied to bovine sperm samples at concentrations of 30, 60, 120, and 240 mM and incubation periods ranging from 5 to 30 minutes. Oxidative stress parameters were assessed by measuring malondialdehyde (MDA) levels and the activities of antioxidant enzymes such as catalase (CAT), glutathione peroxidase (GPx), and reduced glutathione (GSH). Results: NaF exposure led to a significant dose-and time-dependent increase in MDA levels, indicating oxidative stress. This was accompanied by a decrease in CAT and GPx activities and a reduction in GSH levels. The oxidative damage induced by fluoride in sperm cells was further supported by observed declines in sperm motility and viability. Conclusions: NaF exposure disrupts the redox status of bovine sperm cells, leading to oxidative damage and a consequent reduction in fertilization potential. This study highlights the need for further research on chronic fluoride exposure and protective dietary strategies using antioxidants.
Keywords: Fluoride toxicity; Redox homeostasis; Seminal plasma; Oxidative; stress; Antioxidant defense systems; Bulls